2021
DOI: 10.1155/2021/5123823
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Bone Marrow Cell Injection Accelerated Acute Pancreatitis Progression

Abstract: Acute pancreatitis (AP) is one of the leading causes of hospital admission, 20% of which could progress to the severe type with extensive acinar cell necrosis. Clinical studies have reported that diabetes is an independent risk factor of the incidence of AP and is associated with higher severity than nondiabetic subjects. However, how diabetes participates in AP progression is not well defined. To investigate this question, wild-type (wt) and diabetic db/db mice at the age of 16 weeks were used in the study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previously, we showed that injection of BMCs from db/db mice into recipients with caerulein-induced AP resulted in more severe damage than injection of WT BMCs 12 . In this study, we used the same AP model to further compare the disease severity after injection of BMCs isolated from db/db mice at different ages.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we showed that injection of BMCs from db/db mice into recipients with caerulein-induced AP resulted in more severe damage than injection of WT BMCs 12 . In this study, we used the same AP model to further compare the disease severity after injection of BMCs isolated from db/db mice at different ages.…”
Section: Resultsmentioning
confidence: 96%
“…To induce AP, C57BL/6 mice received ten intraperitoneal injections of 50 μg/kg caerulein at 1-hour intervals (Cae, AnaSpec, Inc. San Jose, CA, USA), as previously described 12 . Mice received the same number of PBS injection served as negative controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that immune cells are the main driver of metabolic disorders and inflammation, leading to adverse vascular outcomes. Data from patients and mice with diabetes have consistently demonstrated an increased ratio of myeloid cells to lymphocytes, which further increases with disease progression ( 11 , 12 ). In addition, intracellular levels of GM-CSF and IL-6 were higher in the bone marrow cells of db/db mice than in age-matched wild-type controls ( 12 ), indicating the pathological basis of skewed myelopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients and mice with diabetes have consistently demonstrated an increased ratio of myeloid cells to lymphocytes, which further increases with disease progression ( 11 , 12 ). In addition, intracellular levels of GM-CSF and IL-6 were higher in the bone marrow cells of db/db mice than in age-matched wild-type controls ( 12 ), indicating the pathological basis of skewed myelopoiesis. In line with this, under sustained inflammatory conditions, infiltrating macrophages produce cytokines, such as IL-1β which promotes β cell dysfunction ( 13 ).…”
Section: Discussionmentioning
confidence: 99%